Bioethanol production from potato peel waste using Saccharomyces cerevisiae - Bouhadi Djilali; Larbi Khadidja Side; Belkhodja Hamza; Belmimoun Asmaa; Habib Asmaa; Semmache Amel; Ouahdi Mohamed (Acta Agriculturae Serbica, 2023)
The present work consists of producing bioethanol from potato (Solanum tuberosum L.) peels using Saccharomyces cerevisiae. The different physicochemical and biochemical analyses showed that potato peels are rich in nutritional elements that make them favorable to alcohol fermentation. The total soluble sugars content, the pH value and the ethanol content were evaluated. The results indicated limited ethanol production. The addition of yeast extract, peptone and urea to the fermentation medium improved the ethanol yield produced by the yeast. The physicochemical characterization of purified bioethanol revealed that density, boiling temperature and refractive index are close to those of absolute ethanol. The in vitro antibacterial activity of bioethanol was tested on Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Bacillus subtilis and Bacillus cereus. Significant inhibition zones were observed. This study showed that potato peel waste can be a feedstock for bioethanol production.